Legal Parameters of Placement of Parents in Nursing Homes as Neglect - Rahayu Febriani; Gusti Yosi Andri; Zelfi Ghaffar Aufiya (Ann Publisher, 2026)
Background. The placement of the elderly in nursing homes is still often perceived as a form of neglect, although positive law has not made such an act an automatic offense. The difference between social judgment and legal measures has led to the lack of clear parameters to determine when placement in a nursing home is still an exercise of family obligations and when it turns into neglect. Purpose. This study aims to analyze the legal position of parental placement in nursing homes and formulate the boundary between moral obligations, family legal obligations, and neglect based on Indonesian positive laws through the theory of H.L.A. Hart. Method. This research uses normative legal research methods with a legislative approach and a conceptual approach. The analysis was carried out qualitatively through the interpretation of laws and regulations, legal doctrines, and the theory of H.L.A. Hart as the basis of the analysis. Results. The results showed that the measure of neglect lies in the neglect of the obligation to provide life, care, maintenance, and attention to the elderly who need help, not in the location where they live. Parental placement in a nursing home remains legal as long as the family continues to fulfill legal responsibilities, maintain relationships, supervise treatment, and ensure all parental needs are met. On the other hand, neglect only occurs when the family releases these legal obligations so that the basic needs of the parents are no longer met. Conclusion. This research offers legal parameters that clearly distinguish between moral obligations, family obligations, and neglect, thus providing certainty in the application of laws related to the care of elderly parents.